Enrichment and Quantification of Epitope-specific CD4+ T Lymphocytes using Ferromagnetic Iron-gold and Nickel Nanowires. Issue 1 (December 2018) - Shore, Daniel; Dileepan, Thamotharampillai; Modiano, Jaime; Jenkins, Marc; Stadler, Bethanie
Abstract Epitope-specific CD4+ T lymphocytes were magnetically enriched using ferromagnetic Ni and Fe-Au nanowires coated with a monomer containing a major histocompatibility complex class II-bound peptide epitope (pMHCII). The enriched lymphocytes were subsequently quantified using fluorescence-activated cell sorting (FACS). This was the first use of magnetic nanowires for cell sorting using FACS, and improvements in both specificity and fluorescent signal strength were predicted due to higher particle moments and lengths than conventional paramagnetic beads. Three different types of nanowires (Ni, Fe with Au tip and Fe-Au multilayers) were made by electrodeposition. Ni nanowires separated fewer T cells than Au tipped Fe nanowires, likely because Ni has a lower magnetic moment than Fe. Fe-Au multilayer nanowires separated more T cells than Au-tipped Fe nanowires because there was more monomer per nanowire. Also, increasing the amount of monomer increased the number of CD4+ cells separated. Compared to conventional paramagnetic beads, the nanowires had lower specificity for CD4+ T cells, but had stronger fluorescent signals due to more fluorophores per particle. This results in broader FACS baseline separation between the positive and negative cells, which is useful to detect T cells, even those with lower binding affinity for pMHCII ligands.